Clinical Feature and Treatment Outcomes of Necrotizing Autoimmune Myopathy in a Referral Neurological Center in Thailand - Sirilux Angsuwattanakul; Thanes Termglinjan; Arada Rojana-udomsart (Journal of Clinical Neuromuscular Disease, 2026)
Background: Necrotizing autoimmune myopathy (NAM) is classified into 3 subtypes according to antibodies. Data from Southeast Asian populations remain limited. Objective: To describe and compare clinical characteristics and treatment responses among the NAM subtypes. Methods: Retrospective cohort included three subtypes of 29 patients with NAM. Demographics, clinical data, treatment approach, and responses were assessed and compared. Results: There were 20 (68.97%) anti–signal recognition particle (SRP), 8 anti–hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) (27.59%), and 1 (3.44%) seronegative patients. Anti-SRP, compared with anti-HMGCR patients, tended to be more severe with cardiac and respiratory involvement. They tended to have residual disabilities at 12 months, whereas most anti-HMGCR patients achieved near-complete functional recovery. Associated cancer was found in an anti-HMGCR–associated patient. Rituximab administration in patients who did not respond to first-line therapy resulted in clinical improvement. Conclusions: Patients with anti-SRP–associated NAM were relatively more severe. Cancer screening should be considered in anti-HMGCR patients. Rituximab was beneficial in individual patients.